Triethylamine–Mesyl Chloride/Thionyl Chloride: A Reagent for Hydrodebromination of Diquinane-Based α-Bromo-γ-Lactones - Rao, Chintada Nageswara; Khan, Faiz Ahmed (Synthesis, 2015)
A selective debromination of tetracyclic dibrominated bis-γ-lactones in the presence of triethylamine and mesyl chloride is reported. Both mesyl chloride and triethylamine are essential for the debromination process. The reduction is proposed to proceed through halophilic substitution of electrophilic bromine. The source of the halophile in this reaction is believed to be triethyl(mesyl)ammonium chloride. The nonoccurrence of debromination in dibromo bis-γ-lactones with tosyl chloride and triethylamine as reagents suggests that the formation of a source of well-dissociated chloride ions during the reaction is necessary. Furthermore, selective debromination of dibrominated bis-γ-lactones was also achieved by using pyridine–thionyl chloride as a reagent. Alternatively, potassium chloride–[18-crown-6] was demonstrated to be a suitable source of chloride ion for the reduction of bromolactones.
Keywords: lactones; polycycles; debrominations